2014
DOI: 10.1074/jbc.m114.562249
|View full text |Cite
|
Sign up to set email alerts
|

Negative Regulation of NADPH Oxidase 4 by Hydrogen Peroxide-inducible Clone 5 (Hic-5) Protein

Abstract: Background: Nox4 is known to be regulated primarily at the transcriptional level and regulates myofibroblast differentiation. Results: Nox4 protein expression is suppressed by Hic-5 via Cbl-c-and HSP27-mediated ubiquitination and proteasomal degradation. Conclusion: Nox4 is posttranslationally regulated by Hic-5, and its interacting proteins, Cbl-c and HSP27 regulate myofibroblast differentiation and senescence. Significance: Prosenescence and profibrotic effects of Nox4 may be mitigated by Hic-5-mediated supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 43 publications
4
35
1
Order By: Relevance
“…This model suggests that disruption of isometric tension could be an important therapeutic strategy for fibrotic diseases that occur in skin, as well as in parenchymal organs such as the lung and liver. Our data differ from those of a recent study on pulmonary fibroblasts, in which depletion of Hic-5 augmented both basal α-SMA expression and TGF-β induction of α-SMA after 24 h (Desai et al, 2014). However, when we knocked down Hic-5 in IMR-90 cells with two different siRNA duplexes, we observed the opposite result, namely that the induction of α-SMA after 24 h and 48 h of TGF-β stimulation (2 ng/ml) was reduced in Hic-5-deficient cells.…”
Section: Discussioncontrasting
confidence: 56%
“…This model suggests that disruption of isometric tension could be an important therapeutic strategy for fibrotic diseases that occur in skin, as well as in parenchymal organs such as the lung and liver. Our data differ from those of a recent study on pulmonary fibroblasts, in which depletion of Hic-5 augmented both basal α-SMA expression and TGF-β induction of α-SMA after 24 h (Desai et al, 2014). However, when we knocked down Hic-5 in IMR-90 cells with two different siRNA duplexes, we observed the opposite result, namely that the induction of α-SMA after 24 h and 48 h of TGF-β stimulation (2 ng/ml) was reduced in Hic-5-deficient cells.…”
Section: Discussioncontrasting
confidence: 56%
“…Post-transcriptional regulation of Nox4 in aging (60) and post-translational regulation of Nox4 in aging (14) were also reported. Finally, Sanders et al (45) reported that despite its decrease at the global level, increased association of histone H4K16 in replicative senescent fibroblasts upregulates Nox4 expression, indicating an epigenetic regulation of Nox4 in aging.…”
Section: Discussionmentioning
confidence: 99%
“…Techniques used for estimation of steadystate mRNA levels are similar to those described eleswhere (9). The primers sequences used are as in Table E3.…”
Section: Real-time Pcrmentioning
confidence: 99%
“…Culture techniques are similar to those described earlier by our group (9). Briefly, the fibroblasts were cultured in DMEM (Life Technologies, Grand Island, NY) supplemented with 10% FBS, 100 U/ml penicillin, 100 mg/ml streptomycin, and 250 mg/ml amphotericin-B and were incubated at 37 8 C in 5% CO 2 and 95% air.…”
Section: Cell Culture and Reagentsmentioning
confidence: 99%
See 1 more Smart Citation